Teachers’ perception of artificial intelligence in higher education - Infante Plaza, Ángel (Scripta Mundi, 2023)
At a global level, artificial intelligence is a trending topic, both in the business world and in education. Technology is increasingly becoming part of educational processes, involving both teachers and students. The aim is to utilize these tools to ensure a better educational process and, consequently, better results in higher education. The present study aims to understand the perception of higher education teachers regarding artificial intelligence and, in turn, to gather their different opinions on how it can influence students. A descriptive research approach was employed, using a qualitative method. Semi-structured interviews were conducted with 10 professors from the Urdesa Higher Technological Institute (ITSU) located in the city of Guayaquil. The research results indicated a high percentage of positive perception among teachers regarding the use of artificial intelligence in higher education in Ecuador. It was also highlighted that artificial intelligence can contribute to students’ development in their classes, emphasizing the importance of using it correctly and taking advantage of all its educational benefits. Furthermore, emphasis was placed on fostering digital culture and ensuring innovative education